Bamboo poles tied with spearheads used for breaking the Dahi Handi - Mumbai Archive Project Team (Jio Institute, 2024)
The pot is suspended 20 to 30 feet above the ground. Bamboo poles tipped with spearheads are used to poke the pot in an attempt to puncture it.